ANÁLISIS DE LA VULNERACIÓN DE LOS DERECHOS FUNDAMENTALES EN LOS DELITOS FLAGRANTES - Suarez Pilay, Cesar Byron (2014)
Noting that the Ecuador is a constitutional state of rights justice implicit is that our country is founded on solidarity, dignity, at work, and the prevalence of the general interest which translates into the immediate entry into force of the constitutional rights, but also in the constitutional sanction to the breach of the constitutional duties and that a State of Justice this characterized inter alia by just laws necessary, effective, with penalties commensurate with the offence unlawful act, well written and that are followed by the society as a whole, this means that they are not draconian or weak, unnecessary, difficult to understand or confusing, symbolic or unenforceable. For that reason it is designated to the yearning of all and all Ecuadorians of Justice responsible, within the reach of any person and community without distinction or discrimination of any kind but effective and efficient, participatory, transparent and guarantor of rights. Unfortunately to the address the the issue of the violation of rights in flagrant offences see with sadness that these lyrical set forth are not respected by police officers, prosecutors or judges because each of them in one or another way to trample the rights of the suspect and no one realizes that while these violations affect both the person itself and the development of the criminal proceedings that establishing him for the alleged crime and It is for this reason that the central objective of this research is to determine the degree of responsibility of who violates these rights and whether there is or not a sanction for them for these violations. Finally, it presents the possibility of including certain reforms proposed by the author which are aimed to achieve respect for these rights constitutionally recognized and protected by international law.